2011
DOI: 10.1371/journal.pone.0027114
|View full text |Cite
|
Sign up to set email alerts
|

Recent Loss of Vitamin C Biosynthesis Ability in Bats

Abstract: The traditional assumption that bats cannot synthesize vitamin C (Vc) has been challenged recently. We have previously shown that two Old World bat species (Rousettus leschenaultii and Hipposideros armiger) have functional L-gulonolactone oxidase (GULO), an enzyme that catalyzes the last step of Vc biosynthesis de novo. Given the uncertainties surrounding when and how bats lost GULO function, exploration of gene evolutionary patterns is needed. We therefore sequenced GULO genes from 16 bat species in 5 familie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 29 publications
(57 reference statements)
0
11
0
Order By: Relevance
“…In contrast, intact GULO was recovered from the third oscine species, American crow, and the basal passerine rifleman ( Acanthisitta chloris ) (table S43). Similar to mammals (74), this pseudogenization was caused by the loss of different exons and lethal mutations. We also found purifying selection has dominated GULO evolution, from the ancestral amniote node (d N /d S = 0.096) to ancestral birds (d N /d S = 0.133) and mammals (d N /d S = 0.355), suggesting conservation of the ability to synthesize Vc both before and after avian divergence.…”
Section: Resultsmentioning
confidence: 95%
“…In contrast, intact GULO was recovered from the third oscine species, American crow, and the basal passerine rifleman ( Acanthisitta chloris ) (table S43). Similar to mammals (74), this pseudogenization was caused by the loss of different exons and lethal mutations. We also found purifying selection has dominated GULO evolution, from the ancestral amniote node (d N /d S = 0.096) to ancestral birds (d N /d S = 0.133) and mammals (d N /d S = 0.355), suggesting conservation of the ability to synthesize Vc both before and after avian divergence.…”
Section: Resultsmentioning
confidence: 95%
“…Among the four nonvitamin C synthesizing lineages, the megabat ( P. vampyrus ) has lost this trait most recently, as closely related bats are able to synthesize vitamin C and the Gulo gene is intact in other species of the Pteropus genus ( Cui et al 2011a , b ). Since our simulations showed that there is lower sensitivity to detect genotype–phenotype associations for recent trait losses, we tested if excluding P. vampyrus from the list of trait-loss lineages would increase the sensitivity to detect Gulo exons.…”
Section: Resultsmentioning
confidence: 99%
“…A targeted Gulo knockout in mouse abolishes the ability to synthesize vitamin C (Maeda et al, 2000). Inactivating mutations in the Gulo gene have been identified in several non-synthesizing species (Cui et al, 2011b; Nishikimi et al, 1994; Nishikimi et al, 1992; Ohta and Nishikimi, 1999). We find Gulo inactivation in additional species (Figure S2) and show that Gulo is inactivated in all and only the sequenced non-synthesizers.…”
Section: Resultsmentioning
confidence: 99%